2005
DOI: 10.1081/jfp-200059480
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Water Loss During Frying of Potato Slices

Abstract: The effect of blanching and drying on water loss and oil uptake during potato slice frying was studied. Two pretreatments were carried out for the slices: (i) blanching in hot water at 85°C for 3.5 min; (ii) blanching in hot water at 85°C for 3. 5 min and then, air-dried until a moisture content of 60 % (wet basis) was obtained. A control treatment, consisting of unblanched potato slices not air-dried was also conducted. After the pretreatments, potato slices were deep-fried in sunflower oil at 120, 150, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
46
3
4

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(58 citation statements)
references
References 29 publications
4
46
3
4
Order By: Relevance
“…As a result, this phenomenon increases water content and thus final oil content [5,73]. In vacuum frying, Shyu and Hwang [85] observed that apple chips prepared by direct vacuum frying of blanched sample appeared to have shrinkage on the surface, and if the apple slices are blanched and then frozen prior to vacuum frying, the fried apple chips had a porous sponge-like structure.…”
Section: Blanchingmentioning
confidence: 96%
See 1 more Smart Citation
“…As a result, this phenomenon increases water content and thus final oil content [5,73]. In vacuum frying, Shyu and Hwang [85] observed that apple chips prepared by direct vacuum frying of blanched sample appeared to have shrinkage on the surface, and if the apple slices are blanched and then frozen prior to vacuum frying, the fried apple chips had a porous sponge-like structure.…”
Section: Blanchingmentioning
confidence: 96%
“…In one model, they assumed that the mass transfer takes place only in the axial direction and used the one directional model proposed by Crank [19]. In the second model, they considered that effective moisture diffusion coefficient is no longer a constant value but rather a function of time due to changes in physical properties of the product during frying, and in this case, they used the analytical model proposed by Pedreschi et al [73].…”
Section: Water Lossmentioning
confidence: 99%
“…only when the steam output is reduced, the oil is transferred to the food, this depends on the permeability properties of the crust formed on the surface of the food [13], [14].…”
mentioning
confidence: 99%
“…Algunos autores hablan también de una oxidación terciaria que comprendería las reacciones de polimerización de las fracciones anteriores (Nawar, 2000). Mellema, 2003;Pedreschi et al, 2005b;Pedreschi y Moyano, 2005;Rimac et al, 2004). La fritura al vacío destaca entre los procesos estudiados para conseguir dichos objetivos de mejora de la calidad.…”
Section: Características Y Degradación Del Aceiteunclassified
“…muestra los valores de pérdida de humedad durante el proceso de fritura para los diferentes tratamientos. La evolución que presentan los datos experimentales que muestra la figura es semejante a los reportados en la literatura tanto para procesos convencionales de deshidratación de alimentos (Prothon, 2003;Sacilik y Elicin, 2006), como para fritura (Farkas et al, 1996b;Krokida et al, 2000a;Moreira et al, 1995;Pedreschi y Moyano, 2005b;Sahin et al, 1999;Vitrac et al, 2002). Se puede apreciar que los datos presentan la forma de las curvas típicas de secado en su etapa de velocidad constante, aunque en el caso de la fritura a 165 ºC parece apreciarse el inicio del periodo de velocidad decreciente (a partir de los 8 minutos de tratamiento).…”
Section: Variación De Pesounclassified